1968
DOI: 10.1002/jez.1401670308
|View full text |Cite
|
Sign up to set email alerts
|

Induction of conjugation by chemical agents in Paramecium

Abstract: Induction of conjugation by chemical agents was studied in nine species of Paramecium. KCI + acriflavine + Ca-poor conditions were effective in inducing conjugation in P. caudatum, P . multimicronucleatum, P. aurelia, P. jenningsi and probably in P. h'ichium. KC1 + Ca-poor conditions were effective in P. caudutum, P . traunsteineri and probably in P. hichiurn. KC1 f acriflavine + Ca-poor conditions were also effective in inducing interspecific conjugation. Interaction between complementary mating types is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Chemical induction of conjugation has previously not been successfully achieved in members of the "bursaria" group of Paramecium species, except for one selfing strain in P. trichium (Miyake, 1968). In the work reported here, 36 stocks were examined ( Kitamura (1982Kitamura ( , 1984 reported that mating reactive cells of Paramecium tend to attach on hydrophobic surfaces such as the polystyrene surface and suggested that some kind of hydrophobic interactions on ciliary membranes is involved in the early step of the induction of conjugation.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Chemical induction of conjugation has previously not been successfully achieved in members of the "bursaria" group of Paramecium species, except for one selfing strain in P. trichium (Miyake, 1968). In the work reported here, 36 stocks were examined ( Kitamura (1982Kitamura ( , 1984 reported that mating reactive cells of Paramecium tend to attach on hydrophobic surfaces such as the polystyrene surface and suggested that some kind of hydrophobic interactions on ciliary membranes is involved in the early step of the induction of conjugation.…”
Section: Discussionmentioning
confidence: 88%
“…In these cell unions, exchange of gamete nuclei is blocked because of the failure of face-to-face adhesion of paroral regions and fusion of identical haploid nuclei occurs, leading to the production of completely homozygous progeny, like those found after autogamy (Miyake, 1968). Though many species of Paramecium have been shown to undergo chemically induced conjugation, this has not previously been reported for Paramecium bursaria.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations